PP.36 The Impact of Unexplained Recurrent Miscarriage on Subsequent Pregnancy Outcomes. (26th April 2013) - Dempsey, M; Flood, K; Burke, N; Murray, A; Mullers, S; Cotter, B; Fletcher, P; Geary, M; Malone, FD
Abstract : Aim: We sought to determine subsequent pregnancy outcomes in a cohort of women with a history of unexplained recurrent miscarriage (RM) as compared to healthy pregnancy controls. Study design: This was a prospective cohort study of women attending a dedicated RM clinic in the Rotunda Hospital in 2011. Inclusion criteria included women with a history of three consecutive first trimester losses that were unexplained in the past, no medical intervention and singleton pregnancies only. The inclusion criteria for the healthy controls included no history of stillbirth, intrauterine growth restriction, preeclampsia or preterm labour. Results: Of the 42 women with RM recruited to the study nine (23%) experienced further first trimester miscarriages, one molar and one ectopic pregnancy. The remaining RM cohort with ongoing pregnancies (n = 31) were compared to healthy controls (n = 31) matched for age and BMI. The only statistical difference between the two groups was the earlier mean gestational delivery of the RM group (38 + 2 vs 39 + 4 weeks, p = 0.004) attributed to earlier induction due to their past history. Otherwise there was no significant difference with respect to pregnancy complications, delivery and neonatal outcomes. All of RM patients achieved successful term deliveries with a 74% vaginal delivery rate and a mean birthweight of 3.23 kg. Conclusion: This study re-iterates the reassuring prognosis for women with a history of unexplained RM who undergo supportive care at a dedicated clinic. The majority delivered appropriately grown fetuses at term which was comparable to healthy controls.